Stereotactic body radiation therapy for early-stage non-small cell lung cancer: a single-institutional retrospective analysis of outcomes and prognostic factors - Fu, Chengrui; Dong, Jigang; Li, Chunhui; Wang, Zhongtang; Huang, Wei; Liu, Chengxin; Han, Dan; Zhang, Bin; Li, Baosheng (Frontiers in Oncology, 2025)
BackgroundStereotactic body radiotherapy (SBRT) is a definitive treatment for medically inoperable early-stage non-small cell lung cancer (NSCLC), yet optimal dose selection and prognostic factors in elderly, high-risk populations remain debated. This study evaluates long-term outcomes and predictors of survival in a real-world cohort.MethodsWe retrospectively analyzed 258 patients with T1-2N0M0 NSCLC treated with SBRT at Shandong Cancer Hospital (2017–2022). Inclusion criteria: tumors ≤5 cm, medically inoperable or surgery-refused. Survival outcomes (LC, PFS, CSS, OS) were estimated using Kaplan-Meier curves with log-rank tests. Competing risk regression (Fine-Gray model) was used for cancer-specific survival (CSS), with non-cancer deaths as competing events. Prognostic factors of OS via univariable and multivariable Cox regression. Dose fractionation was individualized (median BED10=100 Gy, range: 75–144 Gy), with strict adherence to RTOG 0236 constraints, using 4D-CT for motion management and daily CBCT for image guidance.ResultsThe cohort comprised predominantly elderly patients (median age: 73 years; 41.5% ≥75 years, 21.3% ≥80 years). At a median follow-up of 38.8 months, 5-year OS, progression-free survival (PFS), local control (LC), and CSS rates were 74.2%, 71.9%, 83.8%, and 84.5% respectively. Competing risks analysis revealed cumulative 5-year cancer-specific mortality of 14.1% (7.6%–20.5%) versus non-cancer mortality of 11.6% (6.8%–16.4%). Multivariable analysis identified lower lobe lung cancer (HR = 2.218, p = 0.014), central tumor location (HR = 2.664, p = 0.003), the larger tumor length (HR = 1.415, p = 0.039), smoking history (HR = 2.328, p = 0.008) and medical inoperable (HR = 2.572, p = 0.007) as independent predictors of poor OS. Despite 21.3% central tumors, toxicity was minimal (grade 3 pneumonitis: 1.6%).ConclusionSBRT achieves durable survival in early-stage NSCLC at our center. Central/lower lobe tumors, bigger tumors, smoking history, and medical inoperable independently predict inferior survival, emphasizing the need for personalized dose escalation strategies or combined treatment modalities.